2014
DOI: 10.1063/1.4896626
|View full text |Cite
|
Sign up to set email alerts
|

Plasma induced DNA damage: Comparison with the effects of ionizing radiation

Abstract: We use human primary fibroblasts for comparing plasma and gamma rays induced DNA damage. In both cases, DNA strand breaks occur, but of fundamentally different nature. Unlike gamma exposure, contact with plasma predominantly leads to single strand breaks and base-damages, while double strand breaks are mainly consequence of the cell repair mechanisms. Different cell signaling mechanisms are detected confirming this (ataxia telangiectasia mutated - ATM and ataxia telangiectasia and Rad3 related - ATR, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…In our study, the combination settings increased p53 expression, which was possibly intertwined with increased γH2AX. Additionally, radiotherapy-induced DNA damage and subsequent misrepair may lead to the formation of complex chromosomal aberrations and micronuclei (MN) that contribute to cell death [42]. For the single treatment regimens (low 3 × 2 Gy fractionated radiotherapy; plasma treatment), a significant change in the number of micronuclei was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the combination settings increased p53 expression, which was possibly intertwined with increased γH2AX. Additionally, radiotherapy-induced DNA damage and subsequent misrepair may lead to the formation of complex chromosomal aberrations and micronuclei (MN) that contribute to cell death [42]. For the single treatment regimens (low 3 × 2 Gy fractionated radiotherapy; plasma treatment), a significant change in the number of micronuclei was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous in vitro studies have proven dose-dependent plasma effects on isolated and cellular DNA. Different research groups focused on complex pathophysiological effects of CAP on isolated [29][30][31][32] and cellular [32][33][34][35] DNA. These findings, which were mainly collected in vitro, have already been partially supported by clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kalghatgi et al [ 7 ] and Lazovic et al [ 77 ] determined that plasma-induced phosphorylation of H2AX is ATR-dependent and not ATM-dependent. In their dose-dependent study of APP treatment of MCF10A human breast epithelial cells in vitro , Kalghatgi et al [ 7 ] observed cell proliferation at low doses and apoptosis at high doses.…”
Section: App Interactions With Cellular Dnamentioning
confidence: 99%